Ca2+ channel subtypes and pharmacology in the kidney - Hayashi, Koichi; Wakino, Shu; Sugano, Naoki; Ozawa, Yuri; Homma, Koichiro; Saruta, Takao (Circulation research, 2007)
A large body of evidence has accrued indicating that voltage-gated Ca(2+) channel subtypes, including L-, T-, N-, and P/Q-type, are present within renal vascular and tubular tissues, and the blockade of these Ca(2+) channels produces diverse actions on renal microcirculation. Because nifedipine acts exclusively on L-type Ca(2+) channels, the observation that nifedipine predominantly dilates afferent arterioles implicates intrarenal heterogeneity in the distribution of L-type Ca(2+) channels and suggests that it potentially causes glomerular hypertension. In contrast, recently developed Ca(2+) channel blockers (CCBs), including mibefradil and efonidipine, exert blocking action on L-type and T-type Ca(2+) channels and elicit vasodilation of afferent and efferent arterioles, which suggests the presence of T-type Ca(2+) channels in both arterioles and the distinct impact on intraglomerular pressure. Recently, aldosterone has been established as an aggravating factor in kidney disease, and T-type Ca(2+) channels mediate aldosterone release as well as its effect on renal efferent arteriolar tone. Furthermore, T-type CCBs are reported to exert inhibitory action on inflammatory process and renin secretion. Similarly, N-type Ca(2+) channels are present in nerve terminals, and the inhibition of neurotransmitter release by N-type CCBs (eg, cilnidipine) elicits dilation of afferent and efferent arterioles and reduces glomerular pressure. Collectively, the kidney is endowed with a variety of Ca(2+) channel subtypes, and the inhibition of these channels by their specific CCBs leads to variable impact on renal microcirculation. Furthermore, multifaceted activity of CCBs on T- and N-type Ca(2+) channels may offer additive benefits through nonhemodynamic mechanisms in the progression of chronic kidney disease.